AACSB International recognises SMU Lee Kong Chian School of Business for promoting impactful research - Singapore Management University (Institutional Knowledge at Singapore Management University, 2019)
The complex needs of business, government, and society must be addressed through multidisciplinary, dynamic, and impactful partnerships. Today, AACSB International (AACSB)—the world’s largest business education network—recognised SMU Lee Kong Chian School of Business among 21 business school collaborations as highlights of its 2019 Innovations That Inspire challenge. An annual initiative, the challenge recognises institutions from around the world who serve as champions of change in the business education landscape. This year’s focus emphasized co-creation of knowledge—one of five opportunities identified in AACSB’s Collective Vision for Business Education. With research and thought leadership as a foundation, the highlighted institutions are engaging in a wide range of collaborative partnerships to support new curriculum, establish new products or services, and impact industry and government policy. SMU Lee Kong Chian School of Business was recognised for promoting impactful research through a series of internal efforts to encourage faculty to re-envision their research agendas within a framework of “Meaningful Impact” on the university and its stakeholders. Implementing the societal impact concept at the business school level was the next step in the idea’s evolution. At its core, the innovation aims to reimagine business research to have societal impact, and to redesign the resourcing process to support this initiative. By placing the faculty at the center of a coordinated institutional infrastructure, business research can indeed generate meaningful impact. For details, please click here.